Frontispiece: Aminoglycoside Conjugation for RNA Targeting: Antimicrobials and Beyond. Issue 54 (25th September 2020) - Aradi, Klara; Di Giorgio, Audrey; Duca, Maria
Abstract : Aminoglycosides are therapeutically useful antibiotics as well as very efficient RNA ligands. They are able to interfere with the translation process in prokaryotes upon binding to bacterial ribosomal RNA (rRNA) thus impairing protein synthesis. The ability of aminoglycosides to bind to various RNAs renders them a great source of inspiration for the synthesis of new binders with improved affinity and specificity toward several therapeutically relevant RNA targets. A description of the synthesis and application of aminoglycoside conjugates is reported in the Review by M. Duca et al. on page 12273 ff.